2021
DOI: 10.4322/bds.2021.e3046
|View full text |Cite
|
Sign up to set email alerts
|

The effect of accelerated aging on the color stability and translucency of novel zirconia reinforced rice husk dental composite resin in different infusion media

Abstract: The effect of accelerated aging on the color stability and translucency of novel zirconia reinforced rice husk dental composite resin in different infusion media O efeito do envelhecimento acelerado na estabilidade de cor e translucidez de uma nova resina composta de casca de arroz reforçada com zircônia em diferentes meios de infusão

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(56 reference statements)
0
0
1
Order By: Relevance
“…In this study, the effect of silica-coating on zirconia by sol-gel process on the color change of zirconia was evaluated. Regarding color stability test, Previous studies suggested that color value of ΔE<1.3 is imperceptible to the human eye, while a value of ΔE>3.7 is considered as clinically undesirable [14]. However, the findings in our study revealed that the highest ΔE values among the three groups were noted in silica-aging group with values of ΔE=3.27 ± 0.72 the color change still below the clinically perceptible threshold.…”
Section: Discussioncontrasting
confidence: 50%
“…In this study, the effect of silica-coating on zirconia by sol-gel process on the color change of zirconia was evaluated. Regarding color stability test, Previous studies suggested that color value of ΔE<1.3 is imperceptible to the human eye, while a value of ΔE>3.7 is considered as clinically undesirable [14]. However, the findings in our study revealed that the highest ΔE values among the three groups were noted in silica-aging group with values of ΔE=3.27 ± 0.72 the color change still below the clinically perceptible threshold.…”
Section: Discussioncontrasting
confidence: 50%